Genetic relationships of Caribbean lowland spiny pocket mice (Heteromys desmarestianus: Rodentia; Heteromyidae): evidence of a distinct mitochondrial lineage - Romero, Andrea; Mort, Mark E.; DeWoody, J. Andrew; Timm, Robert M. (THERYA, 2019)
Genetic studies provide important insights into the evolutionary history and taxonomy of species, allowing us to identify lineages difficult to distinguish morphologically. The relationship among species in the genus Heteromys has been in flux as new species have been described, and candidate species have been suggested in the H. desmarestianus group. One new potential species may be in Costa Rica’s Caribbean lowlands. Herein, we test the phylogenetic relationship of individuals from Costa Rica’s Caribbean lowlands to individuals from throughout the species’ range using mitochondrial sequences from cytochrome-b (cytb). We captured 116 individuals from the lowlands, sequenced their cytb genes, and incorporated 74 GenBank sequences from throughout the species’ range to test if individuals from Costa Rica’s Caribbean lowlands potentially constitute an undescribed species. Our results document a distinct mitochondrial lineage in the Caribbean lowlands of Costa Rica. Our results from extensive sampling within the lowlands show a unique mitochondrial DNA lineage, which may suggest the presence of an undescribed species. The Caribbean lowlands of Costa Rica may hold other cryptic diversity, and further phylogenetic studies should incorporate samples from this area, as it may have a unique evolutionary history.